Dynamics of Endotoxin, Inflammatory Variables, and Organ Dysfunction After Treatment With Antibiotics in an Escherichia coli Porcine Intensive Care Sepsis Model. Issue 7 (July 2018) - Skorup, Paul; Maudsdotter, Lisa; Tano, Eva; Lipcsey, Miklós; Castegren, Markus; Larsson, Anders; Sjölin, Jan
Abstract : Objectives: To investigate the dynamics of antibiotic-induced endotoxin liberation and inflammatory response in vivo in a clinically relevant large animal intensive care sepsis model and whether the addition of an aminoglycoside to a β-lactam antibiotic affects these responses. Design: Prospective, placebo-controlled interventional experimental study. Setting: University research unit. Subjects: Thirty-six healthy pigs administered Escherichia coli as a 3-hour infusion. Interventions: After 2 hours, during E. coli infusion, the animals were exposed to cefuroxime alone, the combination of cefuroxime and tobramycin, or saline. Measurements and Main Results: Plasma endotoxin, interleukin-6, tumor necrosis factor-α, leucocytes, and organ dysfunction were recorded for 4 hours after antibiotic treatment, and differences to the values before treatment were calculated. In vitro experiments were performed to ascertain whether endotoxin is released during antibiotic-induced bacterial killing of this E. coli strain. Despite differences between the treatment arms in vitro, no differences in plasma endotoxin were observed in vivo. Antibiotic-treated animals demonstrated a higher interleukin-6 response ( p < 0.001), greater leucocyte activation ( p < 0.001), and more pronounced deterioration in pulmonary static compliance ( p < 0.01) over time than controls. Animals treated with the combination showed a trend toward less inflammation. Conclusions: Treatment with antibiotics may elicit an increased inflammatory interleukin-6 response that is associated with leucocyte activation and pulmonary organ dysfunction. No observable differences were detected in plasma endotoxin concentrations. The reduction in cefuroxime-induced endotoxin release after the addition of an aminoglycoside in vitro could not be reproduced in this model. Abstract : Supplemental Digital Content is available in the text.